Trends in Anterior Cruciate Ligament Reconstruction in the Last Decade: A Web-Based Analysis - Yucens, Mehmet; Aydemir, Ahmet Nadir (The Journal of Knee Surgery, 2019)
Anterior cruciate ligament (ACL) injury is known to be one of the most common knee joint injuries. ACL reconstruction can be similar to the native ACL in respect of graft morphology, tension, position, and orientation. ACL reconstruction can be applied with different surgery techniques, graft and fixation devices, and rehabilitation as ACL reconstruction is just as important as surgery. Although commonly known as a sports injury, ACL injuries are increasingly seen in the general population. The aim of this study was to investigate the trends in ACL injury treatment in the last decade especially the graft choice. The abstracts of a total of 2,622 papers which stated ACL in the title were investigated through a search on the Web of Knowledge. Main topics were created as the ACL reconstruction theme. ACL reconstruction was examined in the abstracts with graft choice as the main theme followed by single bundle, double bundle, sports, rehabilitation, revision, complication, skeletally immature, biomechanics and kinematics, fixation devices, meniscus, anesthesia and pain, tunnel, cell, and intra-articular injection. Of the total 2,622 documents, 2,129 were original articles and 181 were reviews. Most of the documents, 436 in number (16.6%), were published in the American Journal of Sports Medicine, followed by the Journal of Knee Surgery, Sports Traumatology, Arthroscopy at 264. Of the total documents published, 36.3% were from the United States followed by 8.5% from Japan. The author with the most publications was F.H. Fu with 94 publications followed by B.R. Bach with 41 publications. The hamstring graft was most used at 187 single use and comprising 52% of the total graft combinations. Most papers were published in 2016. In 2012, single and double bundle grafts were determined to a total of 23. The most common title investigated in papers was biomechanics and kinematics with a total of 241 publications followed by rehabilitation at 208. Throughout the years of the study period, the most common graft choice was hamstring autograft. Biomechanics and kinematics was the most common title investigated as biomechanics and rehabilitation are known to be just as important as surgery for a successful outcome and patient satisfaction.
Keywords: anterior cruciate ligament; trends; reconstruction; graft choice